2023
DOI: 10.3390/cryst13091388
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation and Growth Kinetics of Sodium Chloride Crystallization from Water and Deuterium Oxide

James M. Flannigan,
Daniel MacIver,
Hikaru Jolliffe
et al.

Abstract: Despite the ubiquity of the crystallization of sodium chloride (NaCl) throughout history, few detailed, well-controlled quantitative studies of the kinetics of NaCl crystallization have been published. Taking advantage of recent advances in technology such as image analysis for crystallite counting and ‘high-throughput’ techniques for characterizing the highly stochastic nucleation process, we report on a detailed examination of the primary and secondary nucleation kinetics of NaCl, crystallized from solution,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Therefore, the Na 2 SO 4 crystallization was a secondary nucleation process. The growth kinetic equation showed that the supersaturation index was −0.64, which is less than 1, indicating that the growth of Na 2 SO 4 crystals was controlled by surface reactions [31].…”
Section: Crystallization Kinetics Of Na 2 So 4 In Simulated High-sali...mentioning
confidence: 99%
“…Therefore, the Na 2 SO 4 crystallization was a secondary nucleation process. The growth kinetic equation showed that the supersaturation index was −0.64, which is less than 1, indicating that the growth of Na 2 SO 4 crystals was controlled by surface reactions [31].…”
Section: Crystallization Kinetics Of Na 2 So 4 In Simulated High-sali...mentioning
confidence: 99%